The impact of forest reserves on livelihoods of fringe communities in Ghana (Journal of Science and Technology, 2016)
This study looked at how the livelihoods of forest fringe communities have been affected by the constitution of four forest reserves in Brong Ahafo and Ashanti Regions of Ghana. The selection of the reserves for study was based on the fact that the reserves were surrounded by a numberof relatively new and old settlements and have potential for socio-economic activities (agricultural production and ecotourism). Two main research approaches, structured questionnaire and semi-structured interviews were used in the data collection. A structured questionnairetogether with open-ended questions was used to collect quantitative and qualitative information on household and community characteristics, including household incomes, farm sizes and tenancy arrangements. An open-ended questionnaire was designed for selected groups and community leaders to solicit their views and perceptions. The study found that farming was the main occupation of the people with cocoa and oil palm being the major cash crops grown in the area. Food crops grown include plantain, maize, cocoyam, cassava and rice. The major tenancy arrangements include family lands, outright purchase and sharecropping. Environmental problems in the area are decline in soil fertility, soil erosion, deforestation, bush fires and depletion of game and wildlife. Incomes were found to be low resulting in high poverty levels. The study shows that the communities have little role to play in the management of forest reserves.